Factors affecting low back pain occurrence in nurses of Purwokerto Islamic Hospital - Triyono, Hambar; Linggardini, Kris (Proceedings Series on Health & Medical Sciences, 2020)
Low Back Pain (LBP) is one of the pains due to work, usually called lower back pain, and has always become the main cause of a disability, in which its effect has influenced the activities in the workplace. The risk factors influencing the pain occurrence include individual factor (age, gender, years of service, body mass index, smoking habit, exercising habit), psychosocial factor, and occupational factor. The aim of the sesearch was determine the factors influencing low back pain occurrence in nurses of Rumah Sakit Islam Purwokerto. The research used a quantitative descriptive design with a cross-sectional study. The sampling technique was total sampling with 75 respondents. The research instrument was a questionnaire with Chi-Square test. The research result indicates that there is no correlation between the factor of gender (0.648), smoking habit (0.418), and exercise habit (0.484) to low back pain occurrence. This is because the p value from the Chi Square test = 0.05.Mean while, it is found that there is a correlation between the factor of age (0.045), body mass index (0.000), years of service (0.002), occupational (0.002), and psychosocial (0.032) to low back pain occurrence. This is because the p value from the Chi Square test = 0.05. The factors influencing low back pain occurrence in nurses of Rumah Sakit Islam Purwokerto are the factors of age, years of service, body mass index, occupational, and psychosocial.